2010
DOI: 10.1177/0363546510370199
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Anterior-Inferior Glenohumeral Instability Using a Portal at the 5:30-o’Clock Position

Abstract: Arthroscopic repair of anterior-inferior instability using the 5:30-o'clock portal is dependent on anchor type and can show good to excellent results. Because of several coinjuries in anterior-inferior instability, an arthroscopic approach may be required to identify and treat such lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 42 publications
3
48
0
5
Order By: Relevance
“…Several studies have noted that patient age at the time of first dislocation greatly influences the subsequent number of dislocations and have suggested that an increased number of dislocations creates more-severe labral tears. 15 20) Younger age and longer time from initial injury to surgery contribute to the propagation of the injuries, which in turn worsens the present instability. 4 5) However, recent investigations have reported that a history of high-energy trauma to the involved shoulder may also account for extensive lesions and severe instability even after a single dislocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have noted that patient age at the time of first dislocation greatly influences the subsequent number of dislocations and have suggested that an increased number of dislocations creates more-severe labral tears. 15 20) Younger age and longer time from initial injury to surgery contribute to the propagation of the injuries, which in turn worsens the present instability. 4 5) However, recent investigations have reported that a history of high-energy trauma to the involved shoulder may also account for extensive lesions and severe instability even after a single dislocation.…”
Section: Discussionmentioning
confidence: 99%
“… 12 13) As such, other authors believe that reattachment of the concomitant SLAP lesion depends on the age and functional demands of the patient, noting that biceps tenodesis or tenotomy had varied results. Most studies claim that there is no significant difference in the range of motion (ROM), functional scores, and recurrence rates when compared to patients who underwent Bankart repair alone; 8 14 15 16) however, a number of authors have noted several limitations of ROM, especially in external rotation, among those who underwent the combined procedure. 8 17) …”
mentioning
confidence: 99%
“…However, recent studies have shown recurrent rates of 4%–19% [[1]–[5]]. Several factors, including a young age at the time of surgery, male sex, shoulder instability on both sides, joint hyperlaxity, participation in collision sports, early return to contact sports, the size of the humeral defect (Hill-Sachs lesion), and bone defects have been associated with the recurrent instability [[6]–[10]]. In addition, a recent study showed that 55% of the re-dislocations after ABR occurred within the first year, and thereafter, the recurrence rate decreased for up to 5 years [[11]].…”
Section: Introductionmentioning
confidence: 99%
“…Bu yüzden saat 5 ve 5:30 portali tanımlanmıştır. [24] Anterior ve posterior Bankart lezyonuna eşlik eden SLAP lezyonu bulunması halinde patoloji "üçlü labral lezyon" olarak tanımlanır ve labral lezyonların %2,4'ünü oluşturmaktadır. [25] Açık Latarjet prosedürü Latarjet prosedürü, anterior instabilitede üç farklı mekanizma ile işlev görmektedir: (1) Abduksiyon ve eksternal rotasyonda konjuant tendon, eklem kapsülü ve supskapularis üzerine askı mekanizması etkisi gösterir, (2) Glenoid antero-posterior çapı artar, (3) Kapsülün korakoakromial ligamanın güdüğüne onarımı stabilizan etki gösterir.…”
Section: Bankart Ve Slap Lezyonuunclassified